Critical Thinking in Zeiten der Unübersichtlichkeit: Grundzüge eines neuen Lehrveranstaltungskonzepts - Löffler, Winfried 1965- (2024)
Since the curriculum reform in 2021, a course in Critical Thinking has been part of the theological curricula at the University of Innsbruck; it is also frequently enrolled by students from outside the Faculty of Theology. Its introduction follows an existing Anglo-Saxon tradition on the one hand and goes back to experiences in logic teaching on the other. This article analyses the aims, the backgrounds in philosophical anthropology, the history of ideas and the academic and social relevance of Critical Thinking, and considers how it can be suitably implemented in the context of theological studies.   &nbsp
Seit der Curricula-Reform 2021 ist an der Universität Innsbruck eine Lehrveranstaltung Critical Thinking Bestandteil theologischer Curricula; sie wird auch von vielen Studierenden von außerhalb der Theologischen Fakultät nachgefragt. Ihre Einführung schließt einerseits an eine bestehende angelsächsische Tradition an und geht andererseits auf Erfahrungen im Logikunterricht zurück. Der Beitrag analysiert die Ziele, philosophisch-anthropologischen und ideengeschichtlichen Hintergründe sowie die wissenschaftliche und gesellschaftliche Relevanz von Critical Thinking, und er stellt Überlegungen zu einer kontextgerechten Umsetzung im Rahmen theologischer Studien an.
Keywords: Neuropsychologie; Argumentieren; Logik; Kritisches Denken; Critical Thinking